TEACHERS’ COMPETENCE IN A READING TEST CONSTRUCTION - Luthfiyatun Thoyyibah (University of Kuningan, 2022)
Having a certain reading ability is one of the prerequisites for becoming a professional teacher. The focus on language literacy, particularly reading abilities, has been upgraded as well. The focus of this research is to look into the process of developing an English teachers' reading test in vocational schools, and at the same time to investigate the quality of teachers' reading test reflects their ability in test construction. This study employs a case study approach, focusing on three English teachers who work in three distinct vocational schools. This study employs interviews to better understand the process of creating reading tests, as well as thorough expert standards to assess the quality of teacher-created tests. The study discovered that the process of creating a reading test for teachers includes the basic ability to find materials, select the correct text, determine the type of question, and determine the number of digits in the test. Read and rate. As far as the quality of the reading test conducted by the teacher is concerned, the results of the scoring scale show that the teacher’s first reading test is considered poor and good because the passing scores of the test are 69 and 87 respectively. With scores of 51 and 56, reading test number two created by the teacher of English was deemed inadequate. The third teacher's reading test score was 81, so he was considered very good. Other teachers' abilities in test creation have not been effectively utilized in terms of test design, relevance, balance, efficiency, validity, reliability, adequacy of test items, and technical voice of reading test. For reading test, English teachers should use authentic materials. The teacher is also suggested to use real text to create high-level comprehension problems. It is preferable to use a more comprehensive list as one of the study techniques in the future and to involve more participants. Keywords: Reading test; competence; criteria; process of constructing.